2010
DOI: 10.1007/s12199-010-0172-z
|View full text |Cite
|
Sign up to set email alerts
|

A1330V polymorphism of the low-density lipoprotein receptor-related protein 5 gene and bone mineral density in Japanese male workers

Abstract: These findings suggest that LRP5 A1330V polymorphism and exercise may influence BMD in Japanese male workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Additionally, we observed higher levels of TC and HDL‐c levels among individuals with the LRP5‐rs682429 AA or LRP5‐rs312016 GG polymorphisms. A significant association between the LRP5‐rs3736228 and LRP5‐A1330V polymorphisms and hypercholesterolemia has previously been observed. Although the loci we selected were different from those in the above two studies, our results were consistent with their findings, further suggesting that the LRP5 polymorphism is significantly associated with cholesterol levels.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, we observed higher levels of TC and HDL‐c levels among individuals with the LRP5‐rs682429 AA or LRP5‐rs312016 GG polymorphisms. A significant association between the LRP5‐rs3736228 and LRP5‐A1330V polymorphisms and hypercholesterolemia has previously been observed. Although the loci we selected were different from those in the above two studies, our results were consistent with their findings, further suggesting that the LRP5 polymorphism is significantly associated with cholesterol levels.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, LRP5 is also a co-receptor of Wnt/b-catenin signaling (28), a mechanism that might be involved in the development of periodontitis (29). LRP5 polymorphisms have been associated with cholesterol level (30), bone mineral density (31), osteoporosis (32), diabetes mellitus (33), obesity (34), bone fracture (35), Alzheimer's disease (36) and tumors (28,37,38). As a result of the established relationship between periodontitis and osteoporosis, diabetes mellitus and obesity (15,38), we suspect that LRP5 polymorphisms might also be associated with periodontitis.…”
mentioning
confidence: 99%
“…The previous study showed that rs3736228 in the LRP5 gene was strongly associated with the BMD[42]. Through the eQTL analysis, the SNP rs3736228 may serve as a cis-effect regulator of genes CPT1A and MTL5 [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the LRP5 gene, a C→T transition at rs3736228 results in a substitution of Val for Ala, and this transition significantly decreases the response to canonical Wnt signaling ( 23 ). Published data have identified that polymorphisms of rs3736228 are associated with a decrease in bone mineral density in postmenopausal Maya-mestizo females ( 24 ), Mexican females ( 25 ), healthy fertile French females ( 26 ), Japanese male workers ( 27 ), Chinese patients ( 28 ), and Chinese patients with osteoporosis ( 29 , 30 ). However, to date, there are no studies describing an association between rs3736228 polymorphisms and lung cancer.…”
Section: Discussionmentioning
confidence: 99%